Keluarga Sakinah Menurut Pandangan Keluarga Penghafal Al Qur'an - Mohammad Hendy Musthofa (Institut Agama Islam Hasanuddin Pare, 2024)
Sakinah family is the dream of every family, by having a sakinah family it is hoped that the family will be happy both in this world and in the hereafter. To achieve this, one of the provisions needed is an understanding of religious knowledge, so that living your household life does not end in divorce. Family life for those who memorize the Qur'an in Kandat District, Kediri Regency have practiced how to live a sakinah family so that they can become an example for other families. Based on the reasons above the authors conducted this research. The purpose of this research is to find out the sakinah family in the view of families who memorize the Al-Qur'an in Village, Kandat District, Kediri Regency and how are the efforts of families who memorize the Al-Qur'an in Village, Kandat District, Kediri Regency to maintain a sakinah family life. The research conducted was field research using a qualitative approach, with data collection through interviews and direct field observations. Next, it explains descriptively the daily life of a family who memorizes the Al-Qur'an in Village, Kandat District, Kediri Regency based on the values ​​of the Al-Qur'an as a guide in living a sakinah mawaddah warahmah life. The results of this study indicate that a sakinah family according to a family who memorizes the Qur'an in Village, Kandat District, Kediri Regency is living a family's daily life based on the Qur'an, so that every time there is a problem it is always returned to Allah. In their daily routine, they always try to prioritize prayer in congregation and recite the Qur'an, and try to fulfill the rights and obligations between husband and wife.